Creation of Rapid Database Bank Algorithm - Axatovna, Asadova Manzura; Bakhtiyor, Bobokulov; Q.M, Muxamadov; O`tkirovich, Bobojonov Saidjon (European Journal of Life Safety and Stability (2660-9630), 2021)
Today in all sectors of the economy of the Republic of Uzbekistan There have been big changes. Most importantly, data across all networks exchange, creation of a database, integration into a system at a rapid pace being carried out. So there are a number of transitions to a market economy have to solve problems. One such problem is the present from computer programs developed in accordance with modern requirements organize information using and create a unified system of them is calculated. The purpose of developing the database is to process, store, analyze data on a specific land user for the state land cadastre, as well as on individual objects located on land plots and creating software that can be transferred consisted of.